PENGARUH STATUS KESEHATAN TERHADAP HASIL BELAJAR SISWA SD YPK 14 MARANATHA KOTA MANOKWARI - Ruth Faidiban; Hosiana Sombuk (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2017)
Children will develop their abilities both in learning, interacting socially outside the family environment, this happens in the school environment. Parents are required to be able to prepare their children well before entering the school environment, this is so that children can follow the learning process well. School learning outcomes are strongly influenced by the general abilities measured by the intelligence quotient. The purpose of this study was to identify the effect of health status on the learning outcomes of students of the 14th Maranatha YPK Elementary School in Manokwari City. The population in this study were all students in grades 3,4 and 5. Samples were 103 students. The sampling technique is total sampling. The results showed that the health status of students was healthy 78%, while the learning outcomes of 74% were quite good, the results of the analysis showed no effect on health status on student learning outcomes in odd semester with the results of p> 0.05 (p = 0.8) in even semester and p> 0.05 (p = 0.5). It is still necessary to improve the health status of students by emphasizing more on school health efforts in detecting students' health when health problems occur or suffer from illness.